Pictures of a mass-grave and "the scum of Russia". Uit: Wereldkroniek, 25-11-1905. Bottom picture made by Bulla - Bulla, V.K. (1905)
Pictures of a mass-grave and "the scum of Russia". Uit: Wereldkroniek, 25-11-1905. Bottom picture made by Bulla.